Theoretical investigation of injection-locked high modulation bandwidth quantum cascade lasers - Meng, Bo (2013)
In this study, we report for the first time to our knowledge theoretical investigation of modulation responses of injection-locked mid-infrared quantum cascade lasers (QCLs) at wavelengths of 4.6 μm and 9 μm, respectively. It is shown through a three-level rate equations model that the direct intensity modulation of QCLs gives the maximum modulation bandwidths of ~7 GHz at 4.6 μm and ~20 GHz at 9 μm. By applying the injection locking scheme, we find that the modulation bandwidths of up to ~30 GHz and ~70 GHz can be achieved for QCLs at 4.6 μm and 9 μm, respectively, with an injection ratio of 5 dB. The result also shows that an ultrawide modulation bandwidth of more than 200 GHz is possible with a 10 dB injection ratio for QCLs at 9 μm. An important characteristic of injection-locked QCLs is the nonexistence of unstable locking region in the locking map, in contrast to their diode laser counterparts. We attribute this to the ultra-short upper laser state lifetimes of QCLs.